The role of ESRP1 in solid tumor development through the regulation of CD44 splicing and EMT processes - Wang, Lili; Zhang, Min; Zhao, Kelei; Yuan, Xiaohan; Zhao, Houyu; Liu, Yanting; Ji, Yinghua; Lu, Ping (Frontiers in Oncology, 2025)
According to the World Health Organization’s statistics, cancer is the second leading cause of death worldwide, following cardiovascular diseases. Despite significant progress in the field of cancer treatment in recent years, cancer remains one of the main factors shortening human life expectancy. The field of cancer research is increasingly focusing on the role of tumor-related oncogenes and heterogeneous proteins in the development of cancer. Studies indicate that there is a close connection between solid tumors and epithelial splicing regulatory protein 1 (ESRP1). ESRP1 is a key intracellular molecule that plays a crucial role in cell growth and differentiation. As an emerging biomarker, ESRP1 has a decisive impact on the formation and development of solid tumors by regulating the alternative splicing of CD44 and the epithelial-mesenchymal transition (EMT) process. Research shows that abnormal expression of ESRP1 is closely related to the formation and development of various solid tumors, including breast cancer, lung cancer, stomach cancer, and others, and is closely associated with the invasiveness, metastasis, and poor prognosis of tumors. Therefore, given ESRP1’s critical role in cancer development, it is gradually becoming a potential biomarker and therapeutic target. This review primarily discusses the molecular mechanisms of ESRP1 in regulating cancer metastasis, particularly its regulatory effects on CD44 splicing and the EMT process. These research findings provide new targets for cancer treatment, aiming to bring more precise diagnosis and more effective treatment strategies to patients.